Observation of manganese deposits in the Cayman Trough, Caribbean Sea by the ALVIN submersible in 1976 - Heirtzler, James R (Supplement to: Heirtzler, JR (1976): Submersible studies of the Cayman Trough. In: Geodynamics Project U.S. Progress Report - 1976. National Academy of Sciences, Washington D.C., USA; https://catalog.hathitrust.org/Record/007158946, 11-17, https://store.pangaea.de/Projects/NOAA-MMS/Heirtzler_1976_Cayman.pdf, 1976)
Scientists from the Woods Hole Oceanographic Institution, the U.S. Navy, the State University of New York at Albany, Wesleyan University, Oregon State University, Dalhousie University, and the Scripps Institution of Oceanography participated in the Cayman Trough expedition durieng 15 ALVIN dives in January and February 1976. The survey focused on a spreading center is a 150-km section of the plate boundary running across the floor of the Cayman Trough, where two tectonic plates are actually moving apart.